A New Anode for Lithium‐Ion Batteries Based on Single‐Walled Carbon Nanotubes and Graphene: Improved Performance through a Binary Network Design. Issue 9 (16th April 2018) - Ren, Jing; Ren, Rui‐Peng; Lv, Yong‐Kang
Abstract: Carbon nanomaterials, especially graphene and carbon nanotubes, are considered to be favorable alternatives to graphite‐based anodes in lithium‐ion batteries, owing to their high specific surface area, electrical conductivity, and excellent mechanical flexibility. However, the limited number of storage sites for lithium ions within the sp 2 ‐carbon hexahedrons leads to the low storage capacity. Thus, rational structure design is essential for the preparation of high‐performance carbon‐based anode materials. Herein, we employed flexible single‐walled carbon nanotubes (SWCNTs) with ultrahigh electrical conductivity as a wrapper for 3D graphene foam (GF) by using a facile dip‐coating process to form a binary network structure. This structure, which offered high electrical conductivity, enlarged the electrode/electrolyte contact area, shortened the electron‐/ion‐transport pathways, and allowed for efficient utilization of the active material, which led to improved electrochemical performance. When used as an anode in lithium‐ion batteries, the SWCNT‐GF electrode delivered a specific capacity of 953 mA h g −1 at a current density of 0.1 A g −1 and a high reversible capacity of 606 mA h g −1 after 1000 cycles, with a capacity retention of 90 % over 1000 cycles at 1 A g −1 and 189 mA h g −1 after 2200 cycles at 5 A g −1 . Abstract : Batteries not included : Flexible single‐walled carbon nanotubes with ultrahigh electrical conductivity were used as a wrapper for 3D graphene foam to form a binary network structure, which was used as an ultralong‐life anode in lithium‐ion batteries.